2009
DOI: 10.1186/1471-2229-9-38
|View full text |Cite
|
Sign up to set email alerts
|

Plastid chaperonin proteins Cpn60α and Cpn60β are required for plastid division in Arabidopsis thaliana

Abstract: Background: Plastids arose from a free-living cyanobacterial endosymbiont and multiply by binary division as do cyanobacteria. Plastid division involves nucleus-encoded homologs of cyanobacterial division proteins such as FtsZ, MinD, MinE, and ARC6. However, homologs of many other cyanobacterial division genes are missing in plant genomes and proteins of host eukaryotic origin, such as a dynamin-related protein, PDV1 and PDV2 are involved in the division process. Recent identification of plastid division prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 60 publications
2
88
0
2
Order By: Relevance
“…Analysis of the relative protein degradation changes with leaf growth rate (Figure 6) highlighted that while the degradation rate for the majority of the photosynthetic apparatus components positively correlated with growth ( Figure 6A), those of CPN60A and CPN60B negatively correlated with growth. These chaperonins are needed for plastid division (Suzuki et al, 2009), so their increased stabilization and abundance ( Figure 6F) are consistent with the more frequent chloroplast division events that occur in young leaves (Osteryoung and Pyke, 2014). The selective degradation changes observed in younger leaves could also be caused by specific changes in proteolysis and translational control when leaves are growing at a faster rate.…”
Section: Protein Abundance and Turnover Changes In Young Leaves With supporting
confidence: 48%
“…Analysis of the relative protein degradation changes with leaf growth rate (Figure 6) highlighted that while the degradation rate for the majority of the photosynthetic apparatus components positively correlated with growth ( Figure 6A), those of CPN60A and CPN60B negatively correlated with growth. These chaperonins are needed for plastid division (Suzuki et al, 2009), so their increased stabilization and abundance ( Figure 6F) are consistent with the more frequent chloroplast division events that occur in young leaves (Osteryoung and Pyke, 2014). The selective degradation changes observed in younger leaves could also be caused by specific changes in proteolysis and translational control when leaves are growing at a faster rate.…”
Section: Protein Abundance and Turnover Changes In Young Leaves With supporting
confidence: 48%
“…By contrast, the DRP5B level increased, but the FtsZ2-1 (the antibodies are specific to FtsZ2-1 of three FtsZ proteins of Arabidopsis; Suzuki et al, 2009), and ARC6 levels remained constant during leaf development ( Figure 2B). Promoter-b-glucuronidase (GUS) fusion assays also showed that the activity of the PDV2 promoter is highest around the shoot apical meristem, in contrast with the FtsZ and DRP5B promoters ( Figure 2C).…”
Section: Resultsmentioning
confidence: 97%
“…Most wild-type chloroplasts contained only one Z-ring, though occasionally more were observed ( Figure 1C). By contrast, msl2 msl3 mutant chloroplasts frequently contained multiple Z-rings, some with a disorganized, forked appearance, similar to those observed in the arc11, arc3, mcd1, and parc6 mutants but distinct from those observed in other plastid division mutants, such as arc5, plastid division1 plastid division2 (pdv1 pdv2), or arc2 (Vitha et al, 2003;Miyagishima et al, 2006;Glynn et al, 2007Glynn et al, , 2009Fujiwara et al, 2008;Nakanishi et al, 2009a;Suzuki et al, 2009).…”
Section: Msl2 and Msl3 Are Required For Normal Z-ring Placementmentioning
confidence: 90%
“…Many established components of the plastid division apparatus were first identified as mutants with enlarged plastids, including nine arc mutants, cdp1, mcd1, pdv1, and br04 Leech, 1992, 1994;Miyagishima et al, 2006;Nakanishi et al, 2009a;Suzuki et al, 2009;Zhang et al, 2009). In this analysis of msl2 msl3 mutants, FtsZ ring formation was used as a cell-based marker for normal chloroplast division.…”
Section: Defective Chloroplast Division Explains the Enlarged Chloropmentioning
confidence: 99%